Characteristics of online medical care consultation for pregnant women during the COVID-19 outbreak: cross-sectional study. Issue 11 (17th November 2020) - Chen, Miaomiao; Liu, Xiyao; Zhang, Jun; Sun, Guoqiang; Gao, Ying; Shi, Yuan; Baker, Philip; Zeng, Jing; Zheng, Yangxi; Luo, Xin; Qi, Hongbo
Abstract : Objectives: This study described the needs of pregnant women and the contents of online obstetric consultation in representative areas with various severity of the epidemic in China. Design: This was a cross- sectional study. Setting: Yue Yi Tong (YYT), a free online communication platform that allows pregnant women to consult professional obstetricians. Participants: All the pregnant women who used the YYT platform. Intervention: From 10 to 23 February, we collected data on online obstetric consultations and participants' satisfaction through the YYT platform in the mild, moderate and severe epidemic areas which were defined according to the local confirmed cases. The primary outcomes were the reasons for online consultations by the severity of the epidemic. All the comparisons were performed using χ 2 test. Statistical analysis was performed using SPSS V.24. Results: A total of 2599 pregnant women participated in this study, of whom 448 (17.24%), 1332 (51.25%) and 819 (31.51%) were from the mild, moderate and severe epidemic areas, respectively. The distribution of the amount of online consultations was significantly different not only in different areas (p<0.001) but also in different trimesters (p<0.001). A total of 957 participants completed the satisfaction part of the survey. In this study, 77.95% of the participants used e-health for the first time, and 94.63% of the participants were completely or mostly satisfied with the online consultations. Conclusions: The distribution of the amount of online consultations was significantly different not only in different areas but also in different trimesters. In any trimester, the amount of consultations on the second category (obstetric care-seeking behaviour) was the highest in the severe epidemic areas. The needs for online consultations were substantial. In order to prevent irreversible obstetric adverse events, an appropriate antenatal care contingency plan with e-health services is highly recommended during the Public Health Emergency of International Concern.